2015
DOI: 10.3171/2014.10.spine14359
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes after revision lumbar discectomy

Abstract: OBJECT The authors investigated quality of life (QOL) outcomes after primary versus revision discectomy. METHODS A retrospective review was performed for all patients who had undergone a primary or revision discectomy at the Cleveland Clinic Center for Spine Health from January 2008 through December 2011. Among patients in the revision cohort, they identified those who needed a second revision discectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…[262728] In this study, we found an LDH recurrence rate of 11.24% following standard open surgery. These data are in agreement with those of previous studies where the recurrence rate varies between 5% and 15%,[2029] based on the surgical technique employed. We observed that, even if the collected data were statistically significant (Pearson's Chi-square test < 0.001), there was no statistical correlation between the surgical technique employed (discectomy or herniectomy) and the incidence of recurrence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[262728] In this study, we found an LDH recurrence rate of 11.24% following standard open surgery. These data are in agreement with those of previous studies where the recurrence rate varies between 5% and 15%,[2029] based on the surgical technique employed. We observed that, even if the collected data were statistically significant (Pearson's Chi-square test < 0.001), there was no statistical correlation between the surgical technique employed (discectomy or herniectomy) and the incidence of recurrence.…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that a direct correlation between clinical outcome and number of surgical interventions performed exists. [294142] Patients with a better clinical outcome are those with a single surgery or with a surgery for a first recurrence. These data are in agreement with those of the analysis we performed in our study (Pearson's χ 2 < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“… 2 Multiple studies have shown that the outcomes for revision spine surgeries are inferior and have a higher rate of complications compared to primary cases. 5 , 6 Identifying modifiable risk factors for recurrent disc herniation may help surgeons decrease the rate of reoperation and therefore improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 3.0 as the optimal MCID for PHQ-9 (based on calculated SEM), 27,28 as opposed to a value of 5, which has been used for analysis in a number of other studies. [36][37][38][39][40] However, few studies referencing this previous value provided direct evidencebased calculations. Lo ¨we et al's study is one of the few to provide statistically sound establishment of an MCID threshold of 5 for PHQ-9 and is often cited by others.…”
Section: Resultsmentioning
confidence: 99%